Solusi Berkelanjutan untuk Perbaikan Kualitas Innerbox di PT. BKI Surabaya - Ardianto, Rizal; Puspita, Feni Ira; Prahastuti, Ruri Artanti; Fatimah, Siti; Rachmanto, Danny Dwi (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2024)
Surabaya is the center of a growing manufacturing industry that always strives to improve the quality of its products. One company that faces serious problems is PT. BKI, which faces a high rate of innerbox defects with potential negative impact on product quality. The study used Six Sigma methodology to identify and address the root cause of innerbox defects within two months. The results of the analysis show that the main causes of innerbox defects include structuring, material, management, environmental problems, as well as improper assembly methods. The proposed solution involves the use of duplex-type cardboard materials, improved assembly techniques, regular machine maintenance, and environmental control. The use of stripping bands instead of duct tape on innerbox packaging is an effective improvement. The implementation of control for two months showed an increase in sigma value from 2.94 to 2.83. The Six Sigma approach is proven to provide a systematic analytical foundation for significant improvement. The results help PT. BKI in improving quality, efficiency, and customer satisfaction